Above-ground carbon stock in rehabilitated and unrehabilitated mined areas in Mogpog, Marinduque, Philippines - Mante, Katrine Mae B.; Cadiz, Nina M. (Brawijaya University, 2024)
Economic, social, and ecological aspects of the environment are all impacted differently by mining in different parts of the world. When mining activities end and leave the area bare, rehabilitation and revegetation are required to minimize the impacts of mining in general. By fixing carbon in tree biomass, these interventions have a positive effect on increasing carbon storage. Measuring carbon stock is essential to evaluating the effectiveness of these interventions. This study was conducted in an inactive mining area in Marinduque, Philippines. Plots for sampling were created in areas that were not yet undergoing rehabilitation as well as those that were. The above-ground carbon stock and biomass were estimated using the allometric equation provided by IPCC (Intergovernmental Panel on Climate Change) and Sourcebook for Land Use, Land-Use Change and Forestry Projects as references, respectively. The results for areas undergoing rehabilitation and those that were not indicated 4.297 t/ha and 0.0509 t/ha, respectively. The former has an above-ground carbon stock of 2.1485 t/ha, and the latter has 0.2545 t/ha. This shows a successful increase in biomass and carbon stock in the area undergoing rehabilitation. This comparison suggests that rehabilitation and revegetation should be implemented in mining areas to help mitigate the impacts of mining while also sequestering carbon. Policies and activities that will protect the current rehabilitation efforts and expand this rehabilitation to other inactive mining areas should be incorporated for future research.